N‐acetylcysteine improves diabetic associated erectile dysfunction in streptozotocin‐induced diabetic mice by inhibiting oxidative stress. Issue 12 (20th May 2022) - Ma, Zhen; Wang, Wenzhen; Pan, Chao; Fan, Cuiqin; Li, Ye; Wang, Wenjing; Lan, Tian; Gong, Fangxin; Zhao, Changbo; Zhao, Zichao; Yu, Shuyan; Yuan, Mingzhen
Abstract: Oxidative stress appears to play a role in the pathogenesis of diabetes mellitus erectile dysfunction (DMED). This study aimed to investigate the effect of N‐acetylcysteine (NAC) on DMED in streptozotocin‐induced diabetic mice and to explore potential mechanisms. In the present study, we show that an erectile dysfunction is present in the streptozotocin‐induced mouse model of diabetes as indicated by decreases in intracavernous pressure responses to electro‐stimulation as well as from results of the apomorphine test of erectile function. After treatment of NAC, the intracavernous pressure was increased. In these DMED mice, oxidative stress and inflammatory responses were significantly reduced within the cavernous microenvironment, while activity of antioxidant enzymes in this cavernous tissue was enhanced after NAC treatment. These changes protected mitochondrial stress damage and a significant decreased in apoptosis within the cavernous tissue of DMED mice. This appears to involve activation of the nuclear factor erythroid 2‐like‐2 (Nrf2) signalling pathway, as well as suppression of the mitogen‐activated protein kinase (MAPK) p38/ NF‐κB pathway within cavernous tissue. In conclusion, NAC can improve erectile function through inhibiting oxidative stress via activating Nrf2 pathways and reducing apoptosis in streptozotocin‐induced diabetic mice. NAC might provide a promising therapeutic strategy for individuals with DMED.